OC-094 Assessment of obstructive defecation by high resolution manometry compared to magnetic resonance defecography. (28th May 2012) - Heinrich, H; Fruehauf, H; Fried, M; Sauter, M; Fox, M R
Abstract : Introduction: Patients with obstructive defecation may have abnormalities of anorectal function or structure. Standard investigation by manometry shows only fair agreement with patient symptoms and defecography. Anorectal high resolution manometry (HRM) may improve diagnostic accuracy by differentiating pressure effects caused by contraction vs straining and by avoiding movement artifacts. Aims: This study compared HRM findings with magnetic resonance (MR) defecography in the clinical assessment of patients with obstructive defecation defined by Rome III criteria as straining at stool with the sensation of incomplete evacuation, blockage sensation or digital facilitation. Methods: HRM was performed by a solid state catheter with 10 circumferential sensors at 6 mm separation across the anal canal and two placed 5 cm proximal in the rectum (Manoscan AR 360, Given). Resting tone, squeeze pressure and dynamic pressure activity during bearing down were analysed. Findings were referred to MR defecography (1.5T, Philips) performed with 250 ml enema labelled with paramagnetic contrast as reference standard for pelvic floor anatomy and function. Results: 188 consecutive patients (155 female; age 19–93) referred with symptoms of obstructive defecation had full investigation. MRI diagnosis revealed anorectal dyssynergia with paradoxical contraction in 59 and structural pathology in 124 patients (rectocele (n=68) and rectocele with intususception (n=33), pelvic floor descent with enterocele (n=28) or prolapse (n=7), pelvic floor descent (n=87) most patients had multiple pathologies. Five patients were excluded because of inconclusive MRI findings. Compared to patients with dyssynergia, those with structural pathology had lower resting (65 vs 86 mm Hg; p<0.003); and squeeze pressure (150 vs 181 mm Hg; p<0.011). On simulated defecation a negative rectoanal pressure gradient was more evident in dyssynergia than structural pathology (p<0.0001). In patients with dyssynergia on MRI, HRM showed paradoxical contraction or failure to increase abdominal pressure without anal relaxation (sensitivity 100% (59/59); specificity 94% (117/124)). One patient with normal findings on MRI but paradoxical contraction on HRM had an anal fissure. A pattern of high intra-rectal pressure with a steep, positive pressure gradient indicating outlet obstruction in the anal canal was observed on HRM in n=26 patients with rectocele with intussusception on MRI. Conclusion: Diagnostic agreement between anorectal HRM and MR defecography is high and pressure measurements accurately identify recto-anal dyssynergia. A steep intraanal pressure gradient is indicative of outlet obstruction by structural pathology as a cause of obstructive defecation. Competing interests: None declared.